Synthesis of (3E,5E)-1-benzil-3,5 bis (3 (benziloksi)benziliden)piperidin-4-on curcumin analogues and their potential as breast anticancer agents: Assessment using MTT test and molecular docking - Endang Astuti; Jihan Alfiyah Kultsum; Zarah Aulia; Frika Rahmawari; Kasta Gurning; Sugeng Triono; Winarto Haryadi; Harno Dwi Pranowo (Jurnal Pendidikan Kimia, 2024)
Breast cancer is a serious disease that occurs in women and contributes to the highest mortality compared to other types of cancer. This study aims to synthesize curcumin analog compounds ((3E,5E)-1-benzyl-3,5 bis (3 (benzyloxy)benzylidene) piperidin-4-one), test them in vitro against various breast cancer cells (T47D, HER-2, MCF-7, and 4T1) and normal cells (vero cells), and study their molecular docking. Synthesis was carried out by reacting 3-benzyloxybenzaldehyde with N-benzyl-4-piperidone catalyzed by 5% KOH at room temperature; in vitro testing was carried out using the Microculture Tetrazolium Technique Assay method, ADMET analysis with an online database server, and molecular docking studies in Autodoc Vina. The synthesis results obtained yellow solid powder with a yield of 65.85%, characterization with TLC gave black fluorescence (Rf 0.63), melting point 114-116oC, TLC scanner one peak (100%), retention time 0.65 minutes, 1H &13C-NMR analysis showed the molecular formula C40H35NO3, moderate activity against 4T1 breast cancer cells and inactivity on T47D, HER-2, and MCF-7 cancer cells, and did not show cytotoxicity to normal cells (vero cells). ADMET predictions from Lipinski's five rules contained two parameters that did not meet, namely molecular weight and log P value. Molecular docking studies were carried out on estrogen receptor protein (ER)-α (PDB ID: 2ERT), which showed a binding affinity energy of -8.7 kcal/mol and -7.1 kcal/mol of the native ligand. Further research and development is needed on synthetic curcumin analog compounds to increase their activity value against breast cancer by paying attention to Lipinski's five rules to obtain compounds with better potential activity and ADMET.